Congruent movement training as a rehabilitation method to ameliorate symptoms of neglect–proof of concept. (September 2021) - Elshout, Joris A.; Van der Stigchel, Stefan; Nijboer, Tanja C.W.
Abstract: Stroke patients with visuospatial neglect (VSN) have difficulties responding to visual information located in the contralesional hemifield, affecting many daily life activities (ADL) such as eating, reading and mobility. Visual Scanning Therapy (VST) is widely used in clinical practice to ameliorate symptoms of VSN. Yet, not all patients benefit from this training and many training sessions are needed in order to achieve stable results. One potentially promising improvement to the VST is based on the theory that different effectors of the motor systems (e.g., eyes, hands) independently allocate attention during the programming of the movement (i.e., Pre Motor Theory of Attention (PMT)). Here, we studied this direct implementation of the PMT and tested whether a congruent movement training (CMT: congruent -i.e., executed at the same time to the same location-eye and pointing movements) is more effective to attenuate symptoms of neglect compared to VST. This study can be seen as a proof of concept. Attenuation of neglect symptoms was found in the CMT group after just 5 h of training in the subacute phase of neglect. In contrast, no training effects were found in the VST group. These findings indicate the potential of CMT which is a minimal –yet crucial-upgrade of the standard VST protocol that can be easily implemented in the clinic.